LAPTM4B-mediated hepatocellular carcinoma stem cell proliferation and MDSC migration: implications for HCC progression and sensitivity to PD-L1 monoclonal antibody therapy - Haojun Wang; Quanwei Zhou; Ding Fang Xie; Qingguo Xu; Tongwang Yang; Wei Wang (Cell Death and Disease, 2024)
Abstract In hepatocellular carcinoma (HCC), immunotherapy is vital for advanced-stage patients. However, diverse individual responses and tumor heterogeneity have resulted in heterogenous treatment outcomes. Our mechanistic investigations identified LAPTM4B as a crucial gene regulated by ETV1 (a transcription factor), especially in liver cancer stem cells (LCSCs). The influence of LAPTM4B on LCSCs is mediated via the Wnt1/c-Myc/β-catenin pathway. CXCL8 secretion by LAPTM4B drove myeloid-derived suppressor cell (MDSC) migration, inducing unfavorable patient prognosis. LAPTM4B affected PD-L1 receptor expression in tumor microenvironment and enhanced tumor suppression induced by PD-L1 monoclonal antibodies in HCC patients. LAPTM4B up-regulation is correlated with adverse outcomes in HCC patients, sensitizing them to PD-L1 monoclonal antibody therapy.